Cultural Exchange and Its Externalities on Korea-Africa Relations: How Does the Korean Wave Affect the Perception and Purchasing Behavior of African Consumers? - Haggai Kennedy Ochieng; Sungsoo Kim (East Asian Economic Review (EAER), 2019)
The Korean wave has become a global phenomenon whose effect has been widely studied in Asia, Europe and the US. However the presumption of cultural distance makes it appear unlikely that the Korean wave could gain traction among African consumers of cultural products. As such, a dearth of evidence exists on the effects of the wave in Africa. This paper examines the effect of the wave in East African countries employing both descriptive and Probit model analyses. The results show that, contrary to conventional beliefs, most Africans surveyed perceive value proximity with Korea through the values conveyed in Korean dramas, movies and music. Confucius values, such as filial piety, family love and respect for the elderly are the most appealing to the East African audience. Importantly, contact with Korean wave contents contributes to the respondents' disposition to form favorable attitude towards Korea. The African consumers of Korea's cultural products are equally likely to purchase other Korean commercial products. These results remotely suggest that Hallyu may be a tool for advancing Korea's soft power towards Africa and could generate positive economic externalities.
Keywords: F22; F59; Z10; Z11; Z13; Z18; 330; Africa; Korea Wave; Cultural Proximity; Value Proximity; Thematic Proximity; Globalization; Cultural Hybridity